Donor liver histology: a valuable tool in graft selection - Flechtenmacher, Christa; Schirmacher, Peter; Schemmer, Peter (Langenbeck's archives of surgery, 2015)
BackgroundDue to a tremendous organ shortage, livers from donors with extended criteria are increasingly considered for transplantation. Pathologists are more and more requested to evaluate these livers histopathologically using frozen sections at high urgency for acceptability.MethodsThis article reviews the current knowledge on pre-transplant histology in liver transplantation. Prerequisites and conditions for proper pre-transplant evaluation of donor liver tissue are discussed as well as frozen section evaluation and reporting. Data sources include the relevant medical literature, web sites specialized in organ transplantation, and the authors’ experiences in liver transplant centers.ConclusionsPre-transplant histopathological evaluation is a time-effective, accurate, and reliable tool to assess liver quality from candidate deceased donors. Pre-transplant biopsies are of value in the selection of donor livers for transplantation, especially in case of extended criteria donors, and should be performed more frequently in order to avoid unnecessary loss of organs suitable for transplantation and transplantation of inappropriate organs. Correlation of histopathological findings with clinical conditions is essential and requires excellent communication between pathologists, surgeons, and the other members of the transplant team.